2019
DOI: 10.20944/preprints201909.0180.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Albumin-Enriched Fibrin Hydrogel Embedded in Active Ferromagnetic Networks Improves Osteoblast Differentiation and Vascular Self-Organisation

Abstract: Porous coatings on prosthetic implants encourage implant fixation. Enhanced fixation may be achieved using a magneto-active porous coating that can deform elastically in vivo on application of an external magnetic field, straining in-growing bone. Such coating, made of 444 ferritic stainless steel fibres, was previously characterised in terms of its mechanical and cellular responses. In this work, co-cultures of human osteoblasts and endothelial cells were seeded into a novel fibrin-based hydrogel embedded in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Khanna et al also prepared a heat-responsive BSA-based hydrogel, which was shown to be well suitable for topical drug delivery through a series of in vitro and in vivo experiments (Khanna et al, 2020). In addition, BSA-based hydrogels have also been investigated for applications in tissue regeneration, the preparation of thermosensitive or temperaturesensitive hydrogels, the prevention of post-operative adhesions and so on (Arabi et al, 2018;Katarivas Levy et al, 2019;Mao et al, 2021;Yoon et al, 2021).…”
Section: Bsa-based Hydrogelsmentioning
confidence: 99%
“…Khanna et al also prepared a heat-responsive BSA-based hydrogel, which was shown to be well suitable for topical drug delivery through a series of in vitro and in vivo experiments (Khanna et al, 2020). In addition, BSA-based hydrogels have also been investigated for applications in tissue regeneration, the preparation of thermosensitive or temperaturesensitive hydrogels, the prevention of post-operative adhesions and so on (Arabi et al, 2018;Katarivas Levy et al, 2019;Mao et al, 2021;Yoon et al, 2021).…”
Section: Bsa-based Hydrogelsmentioning
confidence: 99%
“…Recently, we demonstrated that human serum albumin (HSA) embedded in a fibrin hydrogel significantly promoted osteoblast differentiation and vascular self-organisation of human endothelial cells 5 . However, high cell numbers (10 6 cells/ml or greater) degrade these fibrin-based hydrogels within 8–10 days making it unsuitable for studying long term bone development and implantation into animal models.…”
Section: Introductionmentioning
confidence: 99%